A review of mechanically stimulated bioluminescence of marine plankton and its applications - Letendre, Francis; Twardowski, Michael; Blackburn, Abigail; Poulin, Carina; Latz, Michael I. (Frontiers in Marine Science, 2024)
Bioluminescence is ubiquitous in marine ecosystems and found in uni- and multicellular organisms. Bioluminescent displays can be used to deter predators, attract mates, and lure and hunt prey. Mechanically stimulated flash kinetics of zooplankton and dinoflagellates are life stage-dependent and species-specific, and could prove effective at identification and monitoring biodiversity in bioluminescent species. Here, we provide a comprehensive review of mechanically stimulated bioluminescence for the main dinoflagellate and zooplankton clades in marine environments and assemble known flash kinetics and spectral emission data. Instruments and methods used in measuring bioluminescence are also discussed. Applications, research gaps, perspectives, and biases in approaches to studying bioluminescence are identified. Moreover, emission kinetics of most zooplankton are very poorly known and constitute a critical gap. Lastly, available knowledge is interpreted in terms of potential future changes in global bioluminescence driven by climate change.